Honoring Roman Emperors in the Jewish Temple: The Salus Augusti in Philo’s Embassy to Gaius - Giambrone, Anthony (Liber annuus, 2024)
Previous scholarship on the Embassy to Gaius has focused heavily upon the emperor’s threat of installing a colossal statue in the Jerusalem Temple, leaving largely unexamined a less obvious, but not less important, conjoined motif: Philo’s prominent staging of the cult of the Salus Augusti. The purpose of the present study is to expose and explore this neglected motif. The analysis will proceed in two stages. After first examining (1) the Salus Augusti devotion as it existed at the time of Gaius Caesar, an investigation of (2) the Embassy’s handling of Gaius’ health will be pursued. The epigraphical and material record will be used in this way to confirm the verisimilitude of the Embassy and thicken its discourse about the emperor/empire’s health. Rhetorically, the Embassy represents a kind of prescription for the sōtēria of Rome. Philo’s Jewish translation of prayers made pro salute Augusti—and not Saluti Augusti—is in its apologetic context inevitably a somewhat opaque redirection. The logic is, nevertheless, clear. Respect for the Jewish religion and people—a sort of philosophical balance of humors—becomes a kind of thermometer measuring the health of the emperor and hence the whole Roman state.